2022
DOI: 10.1186/s12954-022-00590-z
|View full text |Cite
|
Sign up to set email alerts
|

The Bronze Age of drug checking: barriers and facilitators to implementing advanced drug checking amidst police violence and COVID-19

Abstract: Objectives Unpredictable fluctuations in the illicit drug market increase overdose risk. Drug checking, or the use of technology to provide insight into the contents of illicit drug products, is an overdose prevention strategy with an emerging evidence base. The use of portable spectrometry devices to provide point-of-service analysis of the contents of illicit drugs been adopted by harm reduction organizations internationally but is only emerging in the United States. This study aimed to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
84
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(88 citation statements)
references
References 39 publications
(40 reference statements)
1
84
0
Order By: Relevance
“…While our study was not designed to elucidate the specific mechanisms by which OCS led to decreased bridge clinic utilization, in authors’ experience patients reported that incarceration and leaving the area due to fear of incarceration were important factors. Displacement of people from the neighborhood by police, via frequent directives to not to loiter, also likely played a large role [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While our study was not designed to elucidate the specific mechanisms by which OCS led to decreased bridge clinic utilization, in authors’ experience patients reported that incarceration and leaving the area due to fear of incarceration were important factors. Displacement of people from the neighborhood by police, via frequent directives to not to loiter, also likely played a large role [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…They result in more dispersed and less safe disposal of used injection equipment [ 12 ]. The fear and threat of arrest and searches by police can have a chilling effect on the implementation of emerging harm reduction innovations like drug checking [ 13 ]. Though rationalized as public safety actions, sweeps and crackdowns focused on people who use drugs, experience poverty, have marginal housing, and are out in public result in more harm than good [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations